Development of a task-oriented physical education model to enhance students’ intrinsic motivation and motor skills - Priambodo, Anung; Kristyandaru, Advendi; Jannah, Miftakhul; Fathir, Lucy Widya; Orhan, Bekir Erhan; WIbowo, Sapto (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
Physical education serves as a medium to foster the development of motor skills, physical fitness, cognitive abilities, and value appreciation—including attitudes, emotional, spiritual, and social dimensions. This study aimed to examine whether task involvement influences students' intrinsic motivation and motor learning outcomes in physical education. The participants in this research included educational psychology experts, physical education specialists, junior high school physical education teachers in Surabaya, and junior high school students enrolled in Physical Education, Sports, and Health classes. The study involved two classes comprising a total of 70 students. Data were collected through a needs assessment using Focus Group Discussions (FGDs) with experts to explore the importance of innovation in physical education for enhancing intrinsic motivation and motor skill development. The instruments used included an intrinsic motivation questionnaire adapted from the Sport Motivation Scale and a motor ability test administered using the Barrow Motor Ability Test (BMAT), which includes six items. The results yielded a significance value of p = 0.000, indicating a statistically significant difference between pre- and post-test intrinsic motivation scores. In conclusion, the task-oriented physical education learning model was effective in increasing students' intrinsic motivation, making them more satisfied, engaged, and joyful when participating in physical activities at school.